PROPOSTAS DE ADOÇÃO DE TECNOLOGIAS DIGITAIS NO ENSINO DE CONSTRUÇÃO - Leal, Bianca; Salgado, Mônica (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Technologies have significantly altered construction and teaching. However, it is observed that universities are not following the speed of changes, both in curriculum updating and in teacher training. Thus, it is necessary to rethink the training of future professionals so that they enjoy to the maximum the potential offered by technologies in the various fields of architecture and urbanism. In this sense, this paper presents part of the results obtained with the master's research that had as objective to study the alternatives that can be adopted by the professors of the course of architecture and urbanism through the use of digital technologies. In this text will explore the possibilities offered to teaching 'construction'. The technologies used as research cut-off were Building Information Modeling (BIM), Augmented Reality, Virtual Reality, Rapid Prototyping and Digital Manufacturing. The methods adopted were Systematic Review of Literature and literature review without meta-analysis. The results presented tested means and little explored possibilities of use of technologies in the teaching of 'construction'. This study provides a theoretical contribution to the improvement of architectural and urban teaching and, at the same time, it is hoped to encourage teachers to incorporate technologies in the 'building' disciplines.